2013
DOI: 10.1186/1472-6882-13-220
|View full text |Cite
|
Sign up to set email alerts
|

Xiao-Qing-Long-Tang shows preventive effect of asthma in an allergic asthma mouse model through neurotrophin regulation

Abstract: BackgroundThis study investigates the effect of Xiao-Qing-Long-Tang (XQLT) on neurotrophin in an established mouse model of Dermatophagoides pteronyssinus (Der p)-induced acute allergic asthma and in a LA4 cell line model of lung adenoma. The effects of XQLT on the regulation of nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), airway hyper-responsiveness (AHR) and immunoglobulin E were measured.MethodsLA4 cells were stimulated with 100 μg/ml Der p 24 h and the supernatant was collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Several studies also demonstrated the role of BDNF and other neurotrophins in the other chronic respiratory diseases, for example, chronic obstructive pulmonary disease . Moreover, the positive therapeutic effect of different anti‐inflammatory antiasthmatic medicaments is probably mediated through the neurotrophins regulation . A recent study has demonstrated that the monotherapy with salmeterol increased BDNF concentration in serum and platelets which may explain the adverse effect of such monotherapy on the asthmatic airways.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also demonstrated the role of BDNF and other neurotrophins in the other chronic respiratory diseases, for example, chronic obstructive pulmonary disease . Moreover, the positive therapeutic effect of different anti‐inflammatory antiasthmatic medicaments is probably mediated through the neurotrophins regulation . A recent study has demonstrated that the monotherapy with salmeterol increased BDNF concentration in serum and platelets which may explain the adverse effect of such monotherapy on the asthmatic airways.…”
Section: Introductionmentioning
confidence: 99%
“…Lingo-1 (83 kDa) 36 , NgR (51 kDa) 37 , p75 (75 kDa) 38 , TROY (46 kDa) 39 , WNK1 (250 kDa) 31 , and Myt1 (135 kDa) 31 ( Figure 1). 8 …”
Section: Protein Detectionmentioning
confidence: 99%
“…7 8 Another study reported that SCRT exerts a preventive effect against asthma via regulation of neutrotrophin in an allergy-based asthma disease model. 29 In previous clinical studies, Bu-zhong-yi-qi-tang displayed anti-inflammatory activity, suppressing total serum IgE and the IL-4-stimulated production of prostaglandin E2 and leukotriene C4 by polymorphonuclear neutrophils in patients with PAR. 30 In another clinical study, Xin-yi-san was demonstrated to exert an antiallergic effect by enhancing IL-0 and IL-8 production.…”
Section: Discussionmentioning
confidence: 94%